Decline in new drug launches: myth or reality? Retrospective observational study using 30 years of data from the UK. Issue 2 (20th February 2013) - Ward, Derek J; Martino, Orsolina I; Simpson, Sue; Stevens, Andrew J
Abstract : Objective: To describe trends in new drugs launched in the UK from 1982 to 2011 and test the hypothesis that the rate of new drug introductions has declined over the study period. There is wide concern that pharmaceutical innovation is declining. Reported trends suggest that fewer new drugs have been launched over recent decades, despite increasing investment into research and development. Design: Retrospective observational study. Setting and data source: Database of new preparations added annually to the British National Formulary (BNF). Main outcome measures: The number of new drugs entered each year, including new chemical entities(NCEs) and new biological drugs, based on first appearance in the BNF. Results: There was no significant linear trend in the number of new drugs introduced into the UK from 1982 to 2011. Following a dip in the mid-1980s (11–12 NCEs/new biologics introduced annually from 1985 to 1987), there was a variable increase in the numbers of new drugs introduced annually to a peak of 34 in 1997. This peak was followed by a decline to approximately 20 new drugs/year between 2003 and 2006, and another peak in 2010. Extending the timeline further back with existing published data shows an overall slight increase in new drug introductions of 0.16/year over the entire 1971 to 2011 period. Conclusions: The purported 'innovation dip' is an artefact of the time periods previously studied. Reports of declining innovation need to be considered in the context of their timescale and perspective.